Patient´s Awareness and Analysis of Dental Implants Treatment Skill - Aristides da Rosa PINHEIRO; José Jorge SCHOICHET; Eduardo Lúcio SOARES; Cintia Carneiro PINHEIRO (Association of Support to Oral Health Research (APESB), 2006)
Objective: The patients' awareness about the attendance in the clinics of the FOUFF Implatology course, to pursue the betterment of the initial clinical attendance and the progress of previous education. Method: Preceding lectures has been given previously the entrance of the patients in the clinic. A survey about their knowledge before the lectures, and another one with the patients that had presented themselves for the attendance were affected, intending to know the importance of these lectures in the opinion of the patients. Results: Among 721 people who had assisted the previous lectures, 239 (33%) were qualified to be attentive in the clinic. Conclusion: The previous lectures given before the initial clinical attendance had done the patients to be aware of the treatment with implants and it collaborates excessively for the improvement of the attendance and, consequently, also the practical education of the Implantology.